Angle dependent magnetoresistance oscillation study of the Fermi surface of beta''-(BEDT-TTF)(2)AuBr2 - House, A; Blundell, S; Honold, M; Singleton, J; Perenboom, J; Hayes, W; Kurmoo, M; Day, P (1997)
Angle dependent magnetoresistance oscillations (AMRO) have been studied for the charge-transfer salt beta ''-(BEDT-TTF)(2)AuBr2. The temperature range 1.5 K-4.2 K and field region 0.5 T-30 T have been explored. A series of AMRO peaks originating from a similar to 40 T elliptical quasi-two-dimensional (Q2D) Fermi surface (FS) pocket have been observed at all fields. The measured orientation of this pocket is in good agreement with band structure calculations. Above a field of similar to 10 T a second series of(Q2D) AMRO peaks emerge, indicating a field-induced reconstruction of the FS. It is proposed that this results from a shifting of the nesting vector of the spin density wave which is believed to be present in this material. The high field series of peaks correspond to a similar to 222 T elliptical FS pocket with major axis aligned along the direction in which band structure calculations predict Q1D Fermi sheets. It is thus attributed to imperfect nesting of the Q1D FS sheets.